2023
DOI: 10.3390/foods12101973
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Recent Crises on the FLW Consumer Behaviour: A National Wide Representative Research—The Case of Romania

Abstract: Research on food loss and waste (FLW) is quite limited in emerging countries, such as Romania, as the phenomenon, its consequences, and implications are not yet properly understood by both policy makers and consumers. Therefore, the aim of this paper is to conduct representative research in Romania to identify the main clusters of consumers depending on their food waste behaviour. By means of cluster analysis, we highlight the main consumer typologies in Romania, regarding their food waste behaviour. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Firstly, our study did not consider food loss and waste due to the lack of relevant data. Research has shown that reducing food loss and waste can increase self-sufficiency by 20-30% [39,[62][63][64], effectively alleviating the degree of 'hunger' in cities; however, difficulties in obtaining food loss data hinder the implementation of policies for reducing food losses in many countries [65]. The effective acquisition of data on food losses and waste from 'farm to fork' can be considered a critical future research objective, as it is fundamental for exploring and implementing novel food loss reduction technologies, policies, and planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, our study did not consider food loss and waste due to the lack of relevant data. Research has shown that reducing food loss and waste can increase self-sufficiency by 20-30% [39,[62][63][64], effectively alleviating the degree of 'hunger' in cities; however, difficulties in obtaining food loss data hinder the implementation of policies for reducing food losses in many countries [65]. The effective acquisition of data on food losses and waste from 'farm to fork' can be considered a critical future research objective, as it is fundamental for exploring and implementing novel food loss reduction technologies, policies, and planning methods.…”
Section: Discussionmentioning
confidence: 99%
“…This means being a nucleus from a social, economic, political, and environmental perspective in sustainable development. Digitalization brought about certain changes in consumer perspectives when it comes to purchasing tourism products [73]. The blockade caused by COVID-19 encouraged the population to shift towards online shopping and the use of electronic platforms.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Most research in this area relies on a predominantly quantitative approach [13,25,26] based on surveys, while qualitative studies are less common [20,27] with none of them incorporating the sentiment analysis.…”
Section: Introductionmentioning
confidence: 99%